A Hermeneutic Phenomenology: The Death of the Other Understood as Event - Harris B. Bechtol (University of Calgary, 2017)
This is a phenomenological description of what is happening when we experience the death of an other that interprets surviving or living on after such death by employing the term event. This term of art from phenomenology and hermeneutics is used to describe a disruptive and transformative experience of singularity. I maintain that the death of the other is an experience of an event because such death is unpredictable or without a horizon of expectation, excessive or without any principle of sufficient reason, and transformative or a death of the world itself.